The application of the game theory combination weighting-normal cloud model to the quality evaluation of surrounding rocks - Zhao, Bing; Shao, Yang-Bing; Yang, Chao; Zhao, Chao (Frontiers in Earth Science, 2024)
The status of surrounding rocks dramatically influences the safety of construction workers, so the quality assessment of surrounding rocks has great significance. The uniaxial saturated compressive strength of rock (X1), the quality index of surrounding rock (X2), the frictional coefficient of the structural surface (X3), the joint spacing (X4), the state of groundwater(X5), and the integrity coefficient (X6) are selected as the initial evaluation index. Then, the game theory combination weighting-normal cloud model is introduced. Second, the certainty degree matrix of each index is established, and the weight coefficients of assessment indexes are determined based on the game theory combination weighting method. Finally, the quality level of surrounding rocks is judged. Compared with the traditional methods, the proposed model solves the fuzziness and randomness of different indexes, improves the reliability of the assessment process, and enhances the predictive accuracy of assessment results. In addition, it can provide a solution scheme for the evaluation indicators, which are difficult to quantify, and reduce the influence of human factors. The results obtained from the suggested model are consistent with the current specification. Its accuracy approaches 100%, and the method is feasible for the quality level assessment of surrounding rocks, providing a new technique and approach to assessing the risk level of surrounding rocks.